Effectiveness of cognitive approach based on mindfulness of post-traumatic growth and sleep quality of breast cancer survivors - Zamani, Hatef; Bigdeli, Hossein; Tajeri, Biuok; Peymani, Javid (Applied Family Therapy Journal (AFTJ), 2021)
Aim: study was conducted with the aim of determining the effectiveness of cognitive approach based on mindfulness of post-traumatic growth and sleep quality of breast cancer survivors. Method: In a research of the type of experimental studies with a semi-experimental design, 30 women who recovered from breast cancer in Tehran were present and were assigned to two groups. Cognitive therapy based on mindfulness was implemented during 8 sessions on women suffering from cancer, but the control group did not receive any intervention. The data were collected through the post-traumatic growth questionnaire (Tadeschi and Calhoun, 1996) and sleep quality (Pitzborg, 1989) and They were analyzed using analysis of variance with repeated measurements and spss22 software. Results: The findings showed that there is a significant difference between the average of the two experimental and control groups in the variable of post-traumatic growth (F=45.34, P=0.001) and sleep quality (F=42.34, P=0.001), thus, cognitive therapy based on mindfulness on post-traumatic growth and Sleep quality has a significant effect (P<0.05). Conclusion: According to the findings of the research, it can be concluded that the cognitive approach based on the conscious mind is effective in improving the psychological status of women with cancer.